1997
DOI: 10.1177/107769909707400414
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysis of Content Analyses: Twenty-Five Years of Journalism Quarterly

Abstract: Examination of the increasing number of articles employing quantitative content analysis in Journalism & Mass Communication Quarterly showed primary focus on newsleditorial content in U S . media. Nearly half examined newspapers, and half were coauthored. Most used convenience or purposive samples. Few involved a second research method or extra-media data, explicit theoretical grounding, or research questions or hypotheses. Half reported intercoder reliability, and two-fifths used only descriptive statistics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 1 publication
3
44
0
1
Order By: Relevance
“…Many, if not all (Lang, 2013), researchers agree therefore that the psychological discipline examining technological panics is in a Kuhnian preparadigmatic period of science (Kuhn, 1962;Potter, Cooper, & Dupagne, 1993). This idea is supported by metascientific work that has noted that research on media effects uses very little theory (Kamhawi & Weaver, 2003;Riffe & Freitag, 1997).…”
Section: Wheel Reinventionmentioning
confidence: 99%
“…Many, if not all (Lang, 2013), researchers agree therefore that the psychological discipline examining technological panics is in a Kuhnian preparadigmatic period of science (Kuhn, 1962;Potter, Cooper, & Dupagne, 1993). This idea is supported by metascientific work that has noted that research on media effects uses very little theory (Kamhawi & Weaver, 2003;Riffe & Freitag, 1997).…”
Section: Wheel Reinventionmentioning
confidence: 99%
“…Analysis of mediated messages has a long history in communication research and has been steadily evolving as a more sophisticated tool for analysis (Riffe & Freitag, 1997). Recent research has found content analysis to be a key methodology used in many different types of communication studies (Chang & Tai, 2005; Cho & Khang, 2006).…”
Section: A Multifaceted Tool For a Complex Phenomenon: Coding Web‐basmentioning
confidence: 99%
“…The primary purpose of this study is to test a multifaceted and flexible tool for measuring interactive features of Web sites. A tool such as this one is an important “next step” in the evolution of content analysis as that method moves toward more rigorous implementation in online environments (McMillan, 2000b; Riffe & Freitag, 1997; Weare & Lin, 2000). Study of interactivity is also important to the evolving field of online communication (Chang & Tai, 2005; Cho & Khang, 2006; Kim & McMillan, Forthcoming).…”
Section: A Multifaceted Tool For a Complex Phenomenon: Coding Web‐basmentioning
confidence: 99%
“…By concerning big data and new computerized technologies, there are still few studies have drawn on computer-based methods and text analysis (e.g. dictionarybased analysis, topic modeling, network analysis, latent dirichlet analysis, cluster analysis and semantic analysis) (Guo, Vargo, Pan, Ding, & Ishwar, 2016;Lewis, Zamith, & Hermida, 2013;Riffe & Freitag, 1997). These computer-based methods allow researchers to process the Big Data on a real time.…”
Section: Introductionmentioning
confidence: 99%